Analisis Efektivitas Guru Penggerak dalam Meningkatkan Mutu Pembelajaran di SD Negeri 87 Ambon Kecamatan Sirimau Kota Ambon - La Diu Siolimbona; R. Kempa; A. Sahalessy; Sumarni Rumfot (LP. Ma'arif Janggan Magetan, 2024)
The aim of this research is to determine the effectiveness of driving teachers in improving the quality of learning at SD Negeri 87 Ambon, Sirimau District, Ambon City. This research is a qualitative study that describes the effectiveness of driving teachers in improving the quality of learning at SD Negeri 87 Ambon. The subjects in this research consisted of one school principal, one supervisor and 2 driving teachers. The research method in this research is qualitative research. The research is directed at obtaining facts, characteristics and relationships between the events studied by collecting, classifying, presenting and obtaining information regarding the effectiveness of driving teachers in improving the quality of learning at the State Elementary School 87 Ambon, Sirimau District. The results of the research are: 1) Planning the implementation of learning based on a). Results of independent socialization of the independent curriculum; b). Mapping students' learning styles: c). Develop basic competencies and learning objectives: d). Choose a differentiated learning model and e). selection of media and learning resources. 2) Implementation of driving teacher learning using a learning model that is centered and has an impact on students using a differentiated learning model; 3) Assessment and evaluation of learning by directly assessing process differentiation, product differentiation and content differentiation. In the end, the analysis of the effectiveness of motivating teachers in improving the quality of learning at SD Negeri 87 Ambon, Sirimau District, Ambon City shows that motivating teachers have a positive and significant effect in improving the quality of learning in schools. This is proven by the driving teacher having the competence to create student center learning, impact learning on students, create a positive culture, develop students holistically and become a trainer for colleagues.